PENGARUH KINERJA KEUANGAN, DPK DAN JUMLAH SBI TERHADAP PENYALURAN KREDIT PERBANKAN (Studi Pada Bank BUMN Yang Terdaftar di BEI Periode 2009 2018) - Tieka Trikartika Gustyana; Sasdalia Nova Diena (Journal of Management and Business Review, 2020)
The function of the banking sector as an intermediary will lead to activities for banks to raise excess funds in the community and redistribute the funds in the form of credit. Bank lending activities will be influenced by several factors, namely third party funds (DPK), capital adequacy ratio (CAR), return on assets (ROA), non-performing loans (NPLs) and the number of Bank Indonesia certificates (SBI). Based on the results of the study explained that simultaneously DPK, CAR, ROA, NPL and the number of SBI affect the distribution of bank credit. While partially DPK and CAR affects bank lending, while ROA, NPL and the number of SBI does not affect bank lending.